Leadership and Reform in Transitioning Health Systems: Challenges and Imperatives in Australia, New Zealand, and Beyond - Neale Fong (Asia Pacific Journal of Health Management)
In recent years, the landscape of global healthcare has been evolving at a rapid pace, driven by technological advancements, demographic shifts, and changing societal needs. Countries around the world are grappling with similar challenges and trying to navigate the complexities of providing equitable, efficient, and high-quality healthcare to their populations.......